The chain of custody is a necessary condition for the reduction of the risk convicting innocents - Matida, Janaina (2021)
The subject of this paper is chain of custody of evidence. The introductionof this institute in Statute 13.964/19 reflects the recognition that reliability is animportant characteristic of the pieces of evidence that will compose the set of evidenceto be valued by the judge for the determination of the legally relevant facts.The function of the chain of custody of evidence, defined as the chronological documentationof the evidence (which must be understood broadly), is precisely to guaranteethat the piece of evidence which the judge received in the phase of investigationis reliable, was collected, cataloged, manipulated, conditioned, and transportedproperly until it was brought to court; therefore, it can be used as a starting point forevidentiary inferences. In the absence of legislation, I argue that the appropriatephase for examining the chain of custody is the phase of admissibility; and, second,that the consequence of breaking the chain of custody should be the exclusion of thepiece of evidence, avoiding its evaluation. The epistemic quality of the investigativephase is a necessary, albeit not sufficient, condition for a criminal trial seriously committedto the reduction of the risk of convicting innocents.